Investigation of Cu doped cadmium sulphide photoconductive cells - Suchittra Inthong (2020)
© 2019, Chiang Mai University. All rights reserved. Thin film cadmium sulphide photoconductive cells were prepared on clean glass slides by Chemical Bath Deposition (CBD). Copper (Cu) ions were used for doping. Cupric Chloride (CuCl2) and Cadmium Chloride (CdCl2) were mixed with thiourea (CH4N2S) solution. Different amounts of CuCl2 (0.1, 0.2, 0.3 and 0.4 % (molar)) were employed. The annealing temperatures were 300 °C, 400 °C and 500 °C. The XRD analysis revealed that the as-deposited film showed the cubic CdS phase but the hexagonal phase appeared at 300 °C and at higher temperatures. The microstructure study showed that the grain size of 500 °C annealed 0.4 % Cu doped CdS was biggest. Good agreement was found between crystallite size and photosensitivity. With further development by using pair of dopants, this technique could produce better photosensitivity of the CdS cell.